A COMPARATIVE STUDY OF ANTIBIOTIC KNOWLEDGE BETWEEN PHARMACY STUDENTS AT INSTITUT TEKNOLOGI SUMATERA: A COMPARATIVE STUDY OF ANTIBIOTIC KNOWLEDGE BETWEEN PHARMACY STUDENTS AT INSTITUT TEKNOLOGI SUMATERA - Oktariza, Yasinda; Hasanah, Uswatun; Yusuf, Mubarika Sekarsari (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2025)
Abstract Knowledge about antibiotics is one of the key factors that can increase awareness for the appropriate use of antibiotics. Pharmacy students, as part of health-related academic programs, are expected to take on a role in educating the public about appropriate use of antibiotics. This study aims to assess the level of antibiotic knowledge among second-semester and sixth-semester pharmacy students. The research used an observational design with a cross-sectional approach. The study subjects were pharmacy students from the Faculty of Science at Institut Teknologi Sumatera. The research instrument was a questionnaire that had been tested for validity and reliability, and it was distributed online via Google Forms. A total of 219 respondents participated in this study. Data analysis was conducted by comparing the mean total knowledge scores between the two groups using the Mann-Whitney test. The results showed that sixth-semester students had higher knowledge scores compared to second-semester students. Statistically, a significant difference was found (p < 0.001) between the two groups. These findings indicate that the academic level influences knowledge improvement, as senior students have undergone a longer educational and academic process. Overall, pharmacy students have acquired adequate knowledge regarding the proper use of antibiotics. Keywords: antibiotic, knowledge, pharmacy, student